Sejarah Penyusunan Kompilasi Hukum Islam di Indonesia: Analisis Historis dan Yuridis terhadap Kodifikasi dan Integrasinya dalam Sistem Hukum Nasional - Diana Ramadani; Argiya Athala Putri; Ahsin Shidqi; Humaeroh Humaeroh (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This study examines the historical formation and juridical positioning of the Compilation of Islamic Law (Kompilasi Hukum Islam/KHI) within the Indonesian national legal system through a normative qualitative approach. Employing historical and statutory analyses, the research reconstructs the socio-political context underpinning the codification of Islamic law and evaluates its legal legitimacy as a state-recognized instrument. The findings reveal that KHI emerged as a strategic response to the absence of uniformity in judicial decision-making within Religious Courts, which previously relied on diverse classical fiqh references. Its promulgation through Presidential Instruction No. 1 of 1991 signifies a distinctive model of legal integration, reflecting a hybridization of Islamic jurisprudence and national legal principles. The study further demonstrates that KHI functions not only as a practical legal guideline but also as an evolving normative framework shaped by legal pluralism, judicial interpretation, and socio-cultural dynamics. The research contributes to legal scholarship by offering a critical understanding of codification processes in pluralistic legal systems and highlighting the adaptive capacity of Islamic law within modern state structures.